Exercise: A vitally important prescription. Issue 4 (April 2017) - Hechanova, Rachel L.; Wegler, Jennifer L.; Forest, Christopher P.
Abstract : ABSTRACT: Sedentary lifestyles and low physical activity have led to rising health concerns and increasing mortality risks. With the growing concern of the inactivity of adult Americans, it is important that physical activity be promoted to prevent disease and reduce health risks. This article reviews the benefits of physical activity and the steps that primary care providers should take to evaluate physical activity as the fifth vital sign in every patient encounter. The 5A's (assess, advise, agree, assist, and arrange) should be applied in order to implement an exercise prescription into the practice of medicine.